The Effectiveness of an Self Regulated Learning Model Based on Clinical Supervision in Learning Non-Fiction Writing in Private Vocational Schools in Madiun City in the Year 2005/2026 - V. Teguh Suharto; Dwi Setiyadi; Heny Kusumawardani (EDUJAVARE: International Journal of Educational Research, 2026)
To this day, school students still lack the persistence, enthusiasm, and self regulasted in learning that their parents desire. Furthermore, private vocational school students have different educational backgrounds than public vocational school students. Those interested in private vocational schools tend to be those who were not accepted into public vocational schools. A self-directed learning model based on clinical supervision is highly appropriate to address this challenge. Enthusiasm, motivation, persistence, and self regulated learning are instilled through the self-directed learning paradigm, while students are monitored and guided through clinical supervision. Experimental research at Cendekia Vocational School found that the self-directed learning model based on learning assistance is effective for Indonesian language learning in vocational schools in Madiun City.